2017
DOI: 10.17113/ftb.55.04.17.5248
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Whey Protein Concentrates Produced by Ultrafiltration as Primary Raw Materials for Thermal Dairy Gels

Abstract: SummaryThe aim of this work is to study the gelation properties of liquid whey protein concentrates (LWPC) produced by ultrafiltration (UF) as raw material for thermally induced gels intended for food applications. LWPC thermal gelation was performed using different types of LWPC (non--defatted, defatted and diafiltered) of different protein mass fractions and pH. Most of the produced gels showed viscoelastic behaviour. Non-defatted LWPC gave stronger heat-induced gels with a more cohesive microstructure, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…According to rheological properties, in previous work, we obtained similar values for the elastic moduli (G') of thermal dairy gels produced with bovine liquid whey protein concentrates (LWPC) with different levels of fat (non-defatted, 64.3 g kg −1 ; defatted, 4.3 g kg −1 ; diafiltered, 6.0 g kg −1 ). 31 The LWPC presented protein values (wet basis) ranging between 77.5 and 119.3 g kg −1 , similar to those of the whey cheeses tested in the present study, indicating that the protein matrix is the main responsible for the elastic behaviour of the samples. It was also observed that the cultures played an important role in weakening the protein structure because the products WCCK and WCCBB12 showed a lower elastic behaviour and lower values of complex viscosity.…”
Section: Discussionsupporting
confidence: 84%
“…According to rheological properties, in previous work, we obtained similar values for the elastic moduli (G') of thermal dairy gels produced with bovine liquid whey protein concentrates (LWPC) with different levels of fat (non-defatted, 64.3 g kg −1 ; defatted, 4.3 g kg −1 ; diafiltered, 6.0 g kg −1 ). 31 The LWPC presented protein values (wet basis) ranging between 77.5 and 119.3 g kg −1 , similar to those of the whey cheeses tested in the present study, indicating that the protein matrix is the main responsible for the elastic behaviour of the samples. It was also observed that the cultures played an important role in weakening the protein structure because the products WCCK and WCCBB12 showed a lower elastic behaviour and lower values of complex viscosity.…”
Section: Discussionsupporting
confidence: 84%
“…On order to minimise product deterioration, the resting time between whey collection in the production plant and arriving at the pilot plant was less than 2 hours. Non-defatted (ND) liquid whey protein concentrate was produced according the method described by Henriques et al (2017). Firstly, cheese fines were removed by filtration using a cloth filter, and whey was used directly for ultrafiltration (UF) using a pilot plant (Proquiga, Biotech S.A., La Coruña, Spain).…”
Section: Lwpc Manufacturementioning
confidence: 99%
“…A great number of studies have reported on utilizing whey protein (WPI and WPC) or its components, e.g., β-lactoglobulin and bovine serum albumin, in the preparation of protein-based hydrogels and their possible application in the food industry [22] or as delivery systems for drugs or nutrients [33,34]. Although lower values of the swelling ratio for such WPC and WPI hydrogels have been reported (10-100%) [22,34], adding in an absorbent material, such as polysaccharide (e.g., chitosan, CMC), might increase the subsequent swelling ratio by an order of magnitude (100-550%) [35]. Although sweet whey with a high protein content is presently employed in the production of WPI and WPC, low-protein 4…”
Section: Resultsmentioning
confidence: 99%
“…International Journal of Polymer Science acid whey could also constitute a valuable compound for hydrogel synthesis with potential application in agriculture. It has been claimed that assuring the appropriate composition and concentration of proteins (at least 4%) is a requirement for successful gel formation [22]. However, an additional parameter, such as pH, is also a necessity [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation